2020
DOI: 10.3389/fimmu.2020.00592
|View full text |Cite
|
Sign up to set email alerts
|

Current Efforts in the Development of Vaccines for the Prevention of Zika and Chikungunya Virus Infections

Abstract: Arboviruses represent major challenges to public health, particularly in tropical, and subtropical regions, and a substantial risk to other parts of the world as respective vectors extend their habitats. In recent years, two viruses transmitted by Aedes mosquitoes, Chikungunya and Zika virus, have gathered increased interest. After decades of regionally constrained outbreaks, both viruses have recently caused explosive outbreaks on an unprecedented scale, causing immense suffering and massive economic burdens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 204 publications
(191 reference statements)
0
42
0
1
Order By: Relevance
“…Recent data of the clinical trials demonstrated that the vaccine induced a long-term immune response, reducing the risk of symptomatic disease regardless of the person serostatus [ 143 , 144 ]. For ZIKV, no vaccines are available, but several candidates are under development, including in clinical trials [ 133 , 145 , 146 ]. One of those candidates, VRC 705 (National Institute of Allergy and Infectious Diseases/Vaccine Research Center), elicits good immunogenic response, now in phase II clinical trial (NCT03110770) [ 145 , 146 , 147 ].…”
Section: Dengue and Zika Treatments/vaccinesmentioning
confidence: 99%
“…Recent data of the clinical trials demonstrated that the vaccine induced a long-term immune response, reducing the risk of symptomatic disease regardless of the person serostatus [ 143 , 144 ]. For ZIKV, no vaccines are available, but several candidates are under development, including in clinical trials [ 133 , 145 , 146 ]. One of those candidates, VRC 705 (National Institute of Allergy and Infectious Diseases/Vaccine Research Center), elicits good immunogenic response, now in phase II clinical trial (NCT03110770) [ 145 , 146 , 147 ].…”
Section: Dengue and Zika Treatments/vaccinesmentioning
confidence: 99%
“…Climate change, international travel and other unforeseen factors might promote vector emergence and spread in such a way that even developed countries are at risk of becoming endemic for CHIKV, presenting another potential market for a vaccine. The fact that FDA and the EMA have granted Fast Track- and Priority Medicine status to multiple vaccine candidates should inspire further confidence in the for-profit entities regarding the potential market [ 145 ].…”
Section: Current Strategies Against Chikvmentioning
confidence: 99%
“…Recognising the current epidemiological problems and the need for a CHIKV vaccine, the WHO has published a R&D blueprint in which the principles in the design, conduct and analysis of Phase2b/Phase 3 clinical trials to evaluate Chikungunya vaccines are outlined [ 149 ].The WHO’s suggested trial design is a Phase 3 prospective, double-blind, placebo-controlled, efficacy trial [ 149 ]. While this study design is considered the “gold standard” in epidemiologic studies, it seems that the “traditional approval” pathway does not work to receive a BLA for a CHIKV vaccine for various reasons [ 145 ].…”
Section: Current Strategies Against Chikvmentioning
confidence: 99%
“…A single construct recombinant SCV vaccine encoding the structural gene cassettes of both chikungunya virus (CHIKV) and Zika virus (ZIKV) (SCV-ZIKA/CHIK) was constructed with each polyprotein immunogen driven by the same synthetic strong early late promoter [ 20 ], but from two distinct distant loci from within the SCV genome [ 18 ]. A dual ZIKV and CHIKV vaccine was deemed attractive as these virus co-circulate in overlapping geographic regions, and can co-infect both mosquitoes and humans [ 21 23 ]. SCV-ZIKA/CHIK was shown to protect against CHIKV and ZIKV in a series of mouse models [ 18 ].…”
Section: Introductionmentioning
confidence: 99%